Establishing networked misogyny as a counter movement: The analysis of the online anti-Istanbul convention presence. (December 2022) - Eslen-Ziya, Hande
We now live in an age of unhidden gender wars where direct violence occurs within online and offline spaces. These online spaces on Facebook, Twitter or Instagram become venues for attacks on gender and woman's rights, as well as its intersection with race and ethnicity. Such online hate expressions and networked harassments channelled towards women provide clues for us, social scientists, to understand the underlying dynamics/nature of misogyny. In this paper, by studying the online misogynistic narratives developed around the Istanbul Convention as a counter movement, I aim to highpoint the conservative and polarizing discourses that frames gender-based violence as acceptable in Turkey. More specifically I show how Twitter can be used as a platform for anti-feminist and misogynistic groups, aiming violence and hostility directly at women and their rights. As these tweets illustrate, the right-wing populist and anti-gender discourses and conservative and authoritarian politics, are being implemented on many fronts and social media is one of them.